2009
DOI: 10.1016/j.febslet.2009.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Identification of amino acid residues of influenza A virus H3 HA contributing to the recognition of molecular species of sialic acid

Abstract: a b s t r a c tTo identify a determinant of human H3 hemagglutinin (HA) amino acid residues linked to the recognition of molecular species of sialic acid, we generated six mutant viruses possessing either the wild-type HA gene from A/Memphis/1/71 (H3N2) or a genetically single-mutated HA gene at position 137, 144, 155, 158 or 193 from a genetic backbone of A/WSN/33 (H1N1) by reverse genetics. We evaluated the binding ability with four types of synthetic sialylglycolipids. The results indicate that the amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 18 publications
1
31
0
Order By: Relevance
“…Therefore, terminal sialic acids of most Oglycans may convert from Neu5Ac to Neu5Gc. (19). T155Y strongly bound to Neu5Gc␣2,6Gal linkage in addition to Neu5Ac␣2,6Gal linkage (18).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, terminal sialic acids of most Oglycans may convert from Neu5Ac to Neu5Gc. (19). T155Y strongly bound to Neu5Gc␣2,6Gal linkage in addition to Neu5Ac␣2,6Gal linkage (18).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, for comparison of virus infectivity, we used HA mutant IAVs, i.e., strain A/WSN/1933 with a wild-type or single-amino-acid-mutated HA gene of human influenza virus A/Memphis/1/1971 (H3N2). In our previous study, HA of A/Memphis/1/1971, which showed no binding to Neu5Gc, acquired Neu5Gc binding ability by a single-amino-acid mutation, threonine to tyrosine at position 155 in HA (18,19 (19). The two Mem71HA-WSN strains, WT and T155Y, have the wild-type HA of A/Memphis/1/1971 and the HA with a single-amino-acid change of threonine to tyrosine at position 155, respectively (18,19).…”
mentioning
confidence: 99%
“…Furthermore, the use of the purified secretory simian CMAH together with sialyltransferases will enable exogenous addition of Neu5Gc to terminal galactose of glycoconjugates on the surfaces of culture cells, red blood cells and artificial polymers. Neu5Gc-containing glycoconjugates are useful tools for screening of Neu5Gc-binding materials, such as influenza virus [11][12][13][14] and bacterial toxin. 10) Thus, the results of this study will help to advance studies on CMAH enzymatic function, Neu5Gc function and Neu5Gc-binding activity.…”
Section: Discussionmentioning
confidence: 99%
“…10) Some strains of influenza A virus also bind to Neu5Gc. [11][12][13][14] It is thought that Neu5Gc plays a role in the immune system and functions as a microbial (toxin) receptor. However, the biological role of Neu5Gc has not been investigated in detail, compared to the many studies on Neu5Ac.…”
mentioning
confidence: 99%
“…5-N-acetylneuraminic acid and 5-N-glycolylneuraminic acid, where 5-N-glycolylneuraminic acid is an analogue of sialic acid, expressed in many animal tissues, but absent from humans (Chou et al, 1998;Matrosovich et al, 2000;Takahashi et al, 2009). …”
Section: Sequencingmentioning
confidence: 99%